COVID-19 and sustainability in textile, apparel and fashion use: An assessment of trends. Issue 3 (February 2023) - Leal Filho, Walter; Dinis, Maria Alzira Pimenta; do Paço, Arminda; Herédia-Colaço, Vera; Veiga Avila, Lucas; Dennis, Karen; Tyler, David; Neiva, Samara; Liakh, Olena
Apart from the many social and health problems it has caused, the COVID-19 pandemic has had a severe impact on most sectors of the economy worldwide. One of the areas where such impact is noticeable is the textile, apparel, and fashion (TAF) industry. The lockdowns and limited access to retailer outlets resulted in a considerable drop in consumption, creating problems related to the excess of stock, the decrease of sales, and the disposal of non-used items. This paper outlines the implications of the COVID-19 on the TAF sectors and European retailers. It analyzes how the current supply chains exacerbated stock control problems, and it reports on the changes in consumption during the pandemic. The worldwide restrictive measures implemented to cope with the COVID-19 pandemic were responsible for significant profit losses. Also, the decrease in consumption, caused by several geographically wide lockdowns, prompted a subsequent reduction in orders and sales, resulting in a significant number of constraints. The implementation of more environmentally friendly processes, including sustainable circularity as a competitiveness source to keep the TAF sectors in the loop and reduce greenhouse gas emissions, may help address the problems associated with the COVID-19 pandemic in the sustainability context, as reported in this paper.